Role of liquid membrane phenomenon in biological actions of ACE inhibitors, captopril and lisinopril - Nagappa, A.N.; Patil, R.T.; Pandi, P.V.; Ziauddin, K. (National Institute of Science Communication and Information Resources, CSIR, 2001)
The liquid membrane phenomenon in angiotensin converting enzyme (ACE) inhibitors namely, captopril and lisinopril has been studied. Hydraulic permeability data have been obtained to demonstrate the existence of the liquid membrane in series with a supporting membrane generated by the ACE inhibitors. Data on the transport of the relevant permeants in presence of the liquid membrane formed by ACE inhibitors indicate that liquid membrane phenomenon is likely to play a significant role in the action of ACE inhibitors.